Callus Induction of Gendarussa (Justicia gendarussa) by Various Concentration of 2,4-D, IBA, and BAP - Dwi Kusuma Wahyuni; Putri Andriani; Arif Nur Muhammad Ansori; Edy Setiti Wida Utami (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Justicia gendarussa Burm.f., a medicinal plant, is Acanthaceae that has many functions. Furthermore, the compounds in gendarussa must be produced in high quantity and quality by applying callus culture method. Accordingly, it is important to study the effects of plant growth regulators (2,4-D, IBA, and BAP) on callus induction of gendarussa leaves. This research design utilized a factorial design with two factors (2,4-D and IBA: 0.5, 1, 1.5 mg/L and BAP: 0.5, 1, 1.5, 2 mg/L). The experiment consisted of 24 treatments, each of which was repeated 3 times. Observation was carried out in 6 weeks. Data on the time of callus formation, percentage of explants formed callus, and callus morphology were analyzed descriptively,while data on fresh and dry weight were analyzed by Two-Way ANOVA (α = 0.5). Interestingly, the results showed that various concentration of plant growth regulators (2,4-D, IBA, and BAP) affected callus induction from leaf explants of gendarussa. We concluded that the most optimal treatment combination of concentration of plant growth regulators in inducing callus from leaf explants of gendarussa is 1.5 mg/L 2,4-D and 2 mg/L BAP with a relatively long period of callus formation at the earliest, i.e. on day 5, 2.247 g of fresh weight, 0.108 gof dry weight, white callus translucent, and friable. Moreover, the optimum treatment will be used to produce secondary metabolite and seed synthetic by cell suspension culture.